Effect of Spray-Type Alginate Hydrogel Dressing on Burn Wounds - Jeong Yeon Choi; Yong-Joon Joo; Ri Jin Kang; Hee Kyung Jeon; Gyeong Sik Hong (Gels, 2024)
Immediate burn wound care is a critical factor influencing the outcomes of burn treatment. In this study, we developed a spray-type alginate hydrogel dressing that promotes wound healing, reduces pain, and increases the convenience of use in a burn treatment emergency. We investigated the efficiency of newly developed spray-type alginate hydrogel dressing on the wound healing process. We investigated the efficacy of the alginate hydrogel dressing for wound healing in 30 Sprague Dawley rats. Four deep, round second-degree burn wounds (diameter, 1.5 cm) were created bilaterally on the dorsum of the rat’s trunk; the rats were divided into four groups, in which different dressing materials were applied as follows: group A, gauze (control); group B, Mepilex™ (control); group C, 2.25% alginate hydrogel; and group D, 2.5% alginate hydrogel. The gross findings of each group were compared by tracing the remaining wound and performing visual and histological observations and biochemical analysis for proteins associated with wound healing at each time period. In burn wounds, groups C and D showed significantly higher contraction, epithelialization, and healing rates. Histologically, groups C and D showed an improved arrangement of collagen fibers and a thick epithelial layer 14 days after initial wound formation. Group C showed higher CD31, TGF-β, and fibronectin expression in Western blot analyses after day 14. This study suggests that the spray-type alginate hydrogel dressing is an effective material for initial burn wound care.